2013
DOI: 10.5511/plantbiotechnology.13.0909a
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency Agrobacterium-mediated transformation of Cryptomeria japonica D. Don by co-cultivation on filter paper wicks followed by meropenem treatment to eliminate Agrobacterium

Abstract: To develop a more efficient genetic transformation system for Cryptomeria japonica (Japanese cedar), the present study evaluated the effects of culture support during co-cultivation and the use of β-lactam antibiotics (meropenem and carbenicillin) to eliminate Agrobacterium on the transformation efficiency. The co-cultivation of embryogenic tissues and bacterium on filter paper wicks prevented the excess growth of Agrobacterium compared with that observed on solid medium, leading to an increased number of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…From 2016 to 2018, 1857 immature seed explants (except those with microbial contamination), which were collected from 41 artificially pollinated seed families of 2nd generation C. japonica plus trees, were cultured for embryogenic tissues induction. Embryogenic tissue of C. japonica was white to translucent, moist and mucilaginous, and comprised small, dense embryonic cells and elongated, vacuolated suspensor cells (Taniguchi and Kondo 2000), like in other conifers (Jain et al 1995). The embryogenic tissue induction rate (i.e., the percentage of explants forming embryogenic tissue from cultured explants 3 months after the initial culture) in each of the 41 artificially pollinated seed families varied from 3.3 to 86.0% with mean of 38.4% (Figure 1).…”
Section: Embryogenic Tissue Inductionmentioning
confidence: 91%
See 2 more Smart Citations
“…From 2016 to 2018, 1857 immature seed explants (except those with microbial contamination), which were collected from 41 artificially pollinated seed families of 2nd generation C. japonica plus trees, were cultured for embryogenic tissues induction. Embryogenic tissue of C. japonica was white to translucent, moist and mucilaginous, and comprised small, dense embryonic cells and elongated, vacuolated suspensor cells (Taniguchi and Kondo 2000), like in other conifers (Jain et al 1995). The embryogenic tissue induction rate (i.e., the percentage of explants forming embryogenic tissue from cultured explants 3 months after the initial culture) in each of the 41 artificially pollinated seed families varied from 3.3 to 86.0% with mean of 38.4% (Figure 1).…”
Section: Embryogenic Tissue Inductionmentioning
confidence: 91%
“…We conducted a transformation experiment by the methods described by Konagaya et al (2013a) using Agrobacterium (GV3101/pMP90) carrying a binary vector, pZmUbi-GFP-Dt. pZmUbi-GFP-Dt was derived from UbiP-sGFP(S65T)/ HygR (Taniguchi et al 2008) and contains a selection marker hpt and a reporter gene gfp.…”
Section: Gfp Gene Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed method for vector construction is described in Supplementary Information. Transformation of C. japonica ET cell lines expressing GFP were generated through the Agrobacterium-mediated transformation of pZmUbi-GFP-Dt/HygR 24,32 . After screening with 5 mg/L hygromycin, lines with a strong GFP signal with a single-copy line (named N4) were selected through Southern blot analysis ( Supplementary Fig.…”
Section: Vector Constructionmentioning
confidence: 99%
“…Since SE was first reported for spruce species, numerous studies on conifer trees have been reported [ 10 , 11 , 12 ]. For sugi, after the first report on plant regeneration via SE [ 13 ], more results including studies on SE initiation [ 14 , 15 , 16 , 17 , 18 ], somatic embryo maturation [ 19 , 20 , 21 , 22 ], plant conversion [ 9 , 23 ], cryopreservation [ 24 , 25 ], and plant transformation [ 26 , 27 ] were published, showing progress in optimizing SE protocols. However, detailed reports on the factors influencing somatic embryo maturation in several ECLs from different seed families of sugi have not yet been published.…”
Section: Introductionmentioning
confidence: 99%